Pengaruh Layanan Bimbingan Kelompok Teknik Diskusi Terhadap Perilaku Seksual Pranikah Siswa - Oktaviani, Diana; Supriyo, Supriyo (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This research was conducted based on phenomena that occur in grade XI IPS 1 Public high School Negeri Kerjo Kabupaten Karanganyar which has on premarital sexual behavior. The purpose of this study was to determine the effect of guidance service with discussion techniques on premarital sexual behavior. The research subject in this study were students of grade XI IPS 1 Public high School Negeri Kerjo Kabupaten Karanganyar which consist to 15 students were taken using purposive sampling. Methods were using scaling assessment of premarital sexual behavior of students. The data analysis techniques was using wilcoxon match pairs test. The research result showed that sexual behavior before treatment included in in low category and after treatment premarital sexual behavior included in very low category. Wilcoxon match pairs that result showed that Tvalue(0) dan Ttable 5% (25) so that Tvalue< Ttable = 0 < 25which meant Ha was accepted and Ho was rejected. It shows that group guidance service discussion techniques influence on premarital sexual behavior. The conclusion of this research is no effect of group guidance services on premarital sexual behavior